Association Between HTR7 Genetic Polymorphisms and Alcohol Dependence, Using the Alcohol Use Disorders Identification Test (AUDIT). (28th July 2014) - Kim, Jeong‐Hyun; Park, Byung‐Lae; Cheong, Hyun Sub; Bae, Joon Seol; Kim, Lyoung Hyo; Kim, Jee Wook; Lee, Byoung Chul; Seo, Cheong Hoon; Kang, Tae‐Cheon; Park, Sun‐Hee; Choi, Ihn‐Geun; Shin, Hyoung Doo
<x xml:space="preserve">Abstract</x> Background A recent genome‐wide association study has identified 5‐hydroxytrytamine (serotonin) receptor 7, adenylate cyclase‐coupled (HTR7) as a risk gene for alcohol dependence. In addition, the serotonergic system has been considered as a modulator that plays an important role in alcohol use disorders. Functional, pharmacological, and genetic studies of serotonin neurotransmission have revealed that serotonin receptors are potential targets for the treatment of alcohol use disorders. The aim of this study is to investigate whether associations between HTR7 genetic polymorphisms and alcohol dependence could be replicated. Methods This study genotyped a total of 22 common single nucleotide polymorphisms (SNPs) in 459 alcoholic patients and 444 nonalcoholic controls. Results Logistic regression analysis of the case–control study, controlling for age and sex as covariates, showed nominal associations of 7 SNPs (p = 0.02 to 0.04; odds ratio = 0.60 to 1.35). In further linear regression analysis based on the Alcohol Use Disorders Identification Test score for alcohol dependence, 8 SNPs and 3 haplotypes showed relatively significant associations with alcohol dependence (minimum p = 0.001; pcorr = 0.02). Conclusions Although further replications and functional evaluations are needed, our findings suggest that genetic variations of HTR7 may contribute to the predisposition for alcohol dependence.